Narendra Modi: The Transformative Global Leader Redefining 21st Century Governance Excellence - Pallathadka, Harikumar; Roy, Parag Deb (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
This comprehensive research paper presents an exhaustive analysis of Prime Minister Narendra Modi as a transformative global leader who has fundamentally redefined modern governance and international diplomacy. Through the innovative application of the Transformative Federal Leadership (TFL) framework and multiple established leadership theories, this study demonstrates how Modi's leadership exemplifies unprecedented global influence, strategic policy innovation, and diplomatic excellence. Drawing from extensive empirical evidence, international recognition patterns, and comprehensive public perception data spanning 15 years, this analysis establishes Modi as not merely a national leader but as a visionary architect of global governance paradigms. The research conclusively positions Modi as the preeminent transformative leader of the 21st century, whose multidimensional approach has elevated India's global stature while creating replicable models of leadership excellence for the international community.